Mammalian birth versus arousal from hibernation: thyroid hormones, common regulators of metabolic transition? - Melanie Heidkamp; Annika Herwig; Dominique Singer (Journal of Comparative Physiology B, 2025)
Mammalian birth and arousal from hibernation are both endogenously regulated transitional events, characterized by an increase in metabolic rate (MR) and onset of thermogenesis. Thyroid hormones (THs) are known to be key regulators of metabolic and thermogenic activity. To explore the similarities and differences in the role of THs during mammalian birth as opposed to arousal from hibernation, a comprehensive review is given of the levels and kinetics of serum thyrotropin-releasing hormone (TRH), thyroid stimulating hormone (TSH), thyroxine (T 4 ), triiodothyronine (T 3 ), and reverse triiodothyronine (rT 3 ) in hibernating mammals upon arousal and in mammalian neonates at birth. The results for arousal are more heterogeneous than those for birth, reflecting different hibernation patterns between species as well as varying sampling times and methods. Overall, serum TRH concentrations were found to be decreased, TSH unchanged, and T 4 , T 3 , and rT 3 mostly increased. In contrast, the data for mammalian birth show a marked increase in serum levels of TRH, TSH, T 4 , and T 3 , particularly in human neonates, with inconsistent results for rT 3 . In conclusion, both during arousal from hibernation and mammalian birth, THs play a critical yet not exclusive role in metabolic transition. In hibernators, the metabolic effects of THs appear to be mediated by the conversion rates in target tissues rather than by their serum levels alone, suggesting a sustained readiness for arousal. This contrasts with mammalian newborns, who at the beginning of their autonomous life experience the first activation of their thyroid gland, resulting in a transitory “hyperthyroid” state.

Blood transcriptomics mirror regulatory mechanisms during hibernation—a comparative analysis of the Djungarian hamster with other mammalian species - Valeria Rojas Cuyutupa; Dominique Moser; Victoria Diedrich; Yiming Cheng; Jean-Noël Billaud; Elena Haugg; Dominique Singer; Jürgen Bereiter-Hahn; Annika Herwig; Alexander Choukér (Pflügers Archiv - European Journal of Physiology, 2023)
Hibernation enables many species of the mammalian kingdom to overcome periods of harsh environmental conditions. During this physically inactive state metabolic rate and body temperature are drastically downregulated, thereby reducing energy requirements (torpor) also over shorter time periods. Since blood cells reflect the organism´s current condition, it was suggested that transcriptomic alterations in blood cells mirror the torpor-associated physiological state. Transcriptomics on blood cells of torpid and non-torpid Djungarian hamsters and QIAGEN Ingenuity Pathway Analysis (IPA) revealed key target molecules (TM IPA ), which were subjected to a comparative literature analysis on transcriptomic alterations during torpor/hibernation in other mammals. Gene expression similarities were identified in 148 TM IPA during torpor nadir among various organs and phylogenetically different mammalian species. Based on TM IPA , IPA network analyses corresponded with described inhibitions of basic cellular mechanisms and immune system-associated processes in torpid mammals. Moreover, protection against damage to the heart, kidney, and liver was deduced from this gene expression pattern in blood cells. This study shows that blood cell transcriptomics can reflect the general physiological state during torpor nadir. Furthermore, the understanding of molecular processes for torpor initiation and organ preservation may have beneficial implications for humans in extremely challenging environments, such as in medical intensive care units and in space.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)